2017
DOI: 10.1039/c7ra09824c
|View full text |Cite
|
Sign up to set email alerts
|

TiO2nanorod arrays hydrothermally grown on MgO-coated compact TiO2for efficient perovskite solar cells

Abstract: We have demonstrated efficient, stable, and hysteresis-less mesoscopic perovskite solar cells employing TiO2nanorod arrays with MgO modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In the previous reports [10,20] the use of ZnO or MgO coating on TiO 2 surface was found to reduce the recombination process. Growth techniques for example the doctor blade procedure [11], protect printout technique [12], anodization method [13] sol-gel approach [20] have became utilized in favour of the development of TiO 2 thin lms for application in DSCs. Kim et al [14] reported on exible and fabricated solar cells as dye-sensitized through ZnO-modi ed TiO 2 nano-crystal photoelectrodes developed by spraying ethanol solution mixed with ZnCl 2 solution.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the previous reports [10,20] the use of ZnO or MgO coating on TiO 2 surface was found to reduce the recombination process. Growth techniques for example the doctor blade procedure [11], protect printout technique [12], anodization method [13] sol-gel approach [20] have became utilized in favour of the development of TiO 2 thin lms for application in DSCs. Kim et al [14] reported on exible and fabricated solar cells as dye-sensitized through ZnO-modi ed TiO 2 nano-crystal photoelectrodes developed by spraying ethanol solution mixed with ZnCl 2 solution.…”
Section: Introductionmentioning
confidence: 94%
“…These surface-modi ed photoelectrode materials exhibit the enhancement of photo-activityprocess by the degradation of phenolic compounds exspecially in visible region [9]. In the previous reports [10,20] the use of ZnO or MgO coating on TiO 2 surface was found to reduce the recombination process. Growth techniques for example the doctor blade procedure [11], protect printout technique [12], anodization method [13] sol-gel approach [20] have became utilized in favour of the development of TiO 2 thin lms for application in DSCs.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…As reported, one dimensional (1D) nanostructures could offer a straightforward pathway for electron transport, a wide space for effective pore filling of perovskites or hole transport materials, and a large surface area for carrier extraction, thus improving the photovoltaic performance of PSCs . Up to now, different kinds of 1D TiO 2 structures, such as nanorods, nanocone, nanowires, and nanotubes, have been used in PSCs. So far, there are few reports about 1D SnO 2 nanostructured ETMs for PSCs, and neither of them have so satisfactory PCE.…”
Section: Introductionmentioning
confidence: 99%
“…Interfacial diffusion is another widely used method for incorporating dopants, and its doping prole is mainly localized in the vicinity of doping interfaces. [23][24][25] This localized doping method can be adopted for preparing Cs + doped FAPbI 3 layers, which are composed of a Cs + doped underlayer and an undoped capping layer. The undoped part of the perovskite layers tends to preserve the original bandgap of FAPbI 3 , which prevents the blue shi of light absorption by Cs + ion incorporation.…”
Section: Introductionmentioning
confidence: 99%